Model of vegetation extensive system of filters used irrigate crops - Daniela Nicoleta Bădan (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 7th Edition of the International Symposium, November 2016, Bucharest, 2016)
This paper is based on the design of an extensive system of filters vegetation that serves a town with 1,400 inhabitants. In this work I present methods of water purification in rural / urban and viable solutions to implement filters planted with macrophytes based on biological treatment. Depending on the throughput rates of the village wastewater system parameters are established extensive filters. Sewage plants are lower in rural areas usually experiencing considerable seasonal and even daily variations in terms laden with pollutants and sewage flow. The adoption of such methods would bring many benefits to rural areas locally to reduce without the consumption of energy costs if the topography makes it possible plant location and thus decreasing the risks of environmental pollution with the possibility of effective treatment of wastewater. These sewage treatment plants in rural and urban areas must be manageable and exploitable. Ensuring good quality and quantity, purified water is considered a valuable especially in rural areas being reused in agriculture.
Keywords: Q15; Q25; 330; extensive systems; water treatment; sewage plants; rural